2020
DOI: 10.1186/s13045-020-00864-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and rejuvenation strategies for aged hematopoietic stem cells

Abstract: Hematopoietic stem cell (HSC) aging, which is accompanied by reduced self-renewal ability, impaired homing, myeloid-biased differentiation, and other defects in hematopoietic reconstitution function, is a hot topic in stem cell research. Although the number of HSCs increases with age in both mice and humans, the increase cannot compensate for the defects of aged HSCs. Many studies have been performed from various perspectives to illustrate the potential mechanisms of HSC aging; however, the detailed molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 151 publications
(188 reference statements)
2
62
0
Order By: Relevance
“…HSC niches also undergo aging-related structural and functional changes which induce inflammatory challenges to HSCs [ 72 ]. Therefore, we might be able to rejuvenate aged HSCs by improving niche cell function and repressing inflammation in BM [ 12 , 190 ].…”
Section: Age-related Hsc Niche Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSC niches also undergo aging-related structural and functional changes which induce inflammatory challenges to HSCs [ 72 ]. Therefore, we might be able to rejuvenate aged HSCs by improving niche cell function and repressing inflammation in BM [ 12 , 190 ].…”
Section: Age-related Hsc Niche Changesmentioning
confidence: 99%
“…Like most other tissue-specific stem cells, HSCs are vulnerable to aging-related stress and gradually lose their self-renewal and hematopoietic regenerative capacities (HRC) [ 10 12 ]. The process of aging in HSCs is driven by both cell-intrinsic and extrinsic factors, which lead to a reduction in blood cell production and impairment of immune system function [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Old bone marrow contains more HSCs than young bone marrow in both mice and humans [ 11 , 12 , 13 ]. This increase cannot compensate for the defects of aged HSCs and the aged HSC pool contained increased myeloid-dominant HSCs with a lower output of mature blood cells per HSC [ 14 , 15 ]. An increase in proliferation expanded the aged HSC subgroup and induced functional decline of HSCs [ 8 ].…”
Section: General Features Of Hematopoietic Stem Cell (Hsc) Agingmentioning
confidence: 99%
“…HSC self-renewal involved in the maintenance or expansion of stem cell numbers following cellular division. Most HSCs are actively cycling during fetal life and old age, while HSCs in adulthood are often quiescent [ 15 , 46 , 47 , 48 ]. These phenomena were investigated by a serial transplantation assay, which showed that old HSCs had less self-renewal activity and generated smaller daughter clones in extended serial transplants than did their younger counterparts [ 14 ].…”
Section: Regulation Of Hsc Fate During Agingmentioning
confidence: 99%
“…LncRNAs have been illustrated to play a pivotal role in the progression of cell fate and cancer development, including hematopoiesis and leukemogenesis [17,21,24,52]. They exert their functions via cotranscriptional regulation, gene expression modulation, scaffolding of protein complexes, and pairing with other RNAs [22,53].…”
Section: Discussionmentioning
confidence: 99%